School Architecture in Orense during the Second Republic and Franco’s Era: The Case of Bande (BSAA arte, 2019)
In Spain, a large part of the schools created and planned during the Second Republic and, later, during the Franco era, were not carried out. The municipality of Bande (Orense) is a good example of this. It handled works by the renowned architects Pedro Sánchez Sepúlveda, who replaced Antonio Flórez Urdapilleta as head of the Technical Office for School Construction, and Luis Vázquez de Castro and Mariano García Benito, the most influential school architects of the mid-twentieth century in Spain. These were joined by the work of the architects Mariano Rodríguez Sanz and José Barreiro Vázquez.
Keywords: school architecture; Pedro Sánchez Sepúlveda; Luis Vázquez de Castro; Mariano García Benito; Mariano Rodríguez Sanz; José Barreiro Vázquez